Milly, Molly and Junior Joe - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z.)
Milly and Molly help Junior Joe change his lifestyle so he can join in the sports at school. Includes teaching guide. Suggested level: junior